Effects of salinity and shaking condition on the growth and virulence of Vibrio parahaemolyticus - Ngoc My Hanh, Tran; Van Nhi, Tran; Thi Thu Hoai, Nguyen (Vietnam Journal of Biotechnology, 2020)
Vibrio parahaemolyticus is a Gram-negative halophilic bacterium that is found in estuarine, marine and coastal environment. This organism is the major causative agent of Early Mortality Syndrome (EMS) or Acute Hepatopancreatic Necrosis Disease (AHPND) which resulted in serious damages to cultured shrimp industry. Understanding the effect of environmental factors on the growth and virulence of this potential pathogen would be beneficial for preventing its outbreak. In this study, the growth and virulence of V. parahaemolyticus was examined under different salinity and shaking condition. V. parahaemolyticus XN9 was cultured in Brain Heart Infusion (BHI) medium with different sodium chloride concentrations (2.0, 2.5 and 3.0%) and different shaking conditions (0, 120 and 240 rpm). The growth of the bacterium was recorded over 8h and six extracellular enzymes of V. parahaemolyticus XN9 including caseinase, hemolysin, lecithinase, lipase, gelatinase, chitinase were investigated using agar-based method. The growth of V. parahaemolyticus was varied among different salinity and shaking conditions. It showed the best growth at 2.0% NaCl and 240 rpm. No change in the enzymatic activity (EA) of the tested extracellular enzymes was observed while changing salinity except the significant decline of gelatinase from 3.49±0.19 to 2.77±0.17 mm following salinity increase (p < 0.05). On the other hand, regarding shaking condition, lipase was the one to increase its activity significantly following the increase of shaking speed (p < 0.05). While caseinase, lecithinase, gelatinase and lipase were well expressed in V. parahaemolyticus, no hemolytic and chitinase activity was observed in any tested conditions. In summary, our study showed that 2.0 % NaCl and 240 rpm shaking promoted the best growth of V. parahaemolyticus and resulted in highest activity of gelatinase and lipase in this bacterium.